If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -5 * 2 = 0 Multiply -5 * 2 2x + -10 = 0 Reorder the terms: -10 + 2x = 0 Solving -10 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 2x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 2x = 0 + 10 2x = 0 + 10 Combine like terms: 0 + 10 = 10 2x = 10 Divide each side by '2'. x = 5 Simplifying x = 5
| 16x^2+80x+100-3x=17+6x | | -3x+5=17 | | 110-3x=3x+20 | | 2(3x-10)=20 | | 4x+10*4x+10-3x=17+6x | | 3(6x-1)=8(2x-1) | | 105-4x=10x+21 | | 17+2n=21-2n | | 12r-1=11 | | 2(8+n)=22 | | 12x+3=10x+9 | | X+x^2+x^3+x^4=36 | | 4x-3=2x+15 | | x+1+x^2+1=16 | | 63-2x-x^2=0 | | -x-5+4x=-7x+6x+15 | | 81-4x=23x+15 | | 2x^2+14x=-3 | | X^2+8=19 | | 3x(x+1)(7x-2)=0 | | 47k=517 | | x^2-3x=6 | | 16q=272 | | X^2+10+9x=18 | | 3-4x=10x+10 | | 3x+13=-57-7x | | x^2+y^2=25 | | Y=2x+6 | | 8x+5=4x+17 | | 5(5x-4)+x(4x+3)= | | 3x^2-15x-18=0 | | 72-3x=6x+22 |